Collaborative Control of Cell Cycle Progression by the RNA Exonuclease Dis3 and Ras Is Conserved Across Species - Snee, Mark J. (Genetics, 2016)
Dis3 encodes a conserved RNase that degrades or processes all RNA species via an N-terminal PilT N terminus (PIN) domain and C-terminal RNB domain that harbor, respectively, endonuclease activity and 3′–5′ exonuclease activity. In Schizosaccharomyces pombe, dis3 mutations cause chromosome missegregation and failure in mitosis, suggesting dis3 promotes cell division. In humans, apparently hypomorphic dis3 mutations are found recurrently in multiple myeloma, suggesting dis3 opposes cell division. Except for the observation that RNAi-mediated depletion of dis3 function drives larval arrest and reduces tissue growth in Drosophila, the role of dis3 has not been rigorously explored in higher eukaryotic systems. Using the Drosophila system and newly generated dis3 null alleles, we find that absence of dis3 activity inhibits cell division. We uncover a conserved CDK1 phosphorylation site that when phosphorylated inhibits Dis3’s exonuclease, but not endonuclease, activity. Leveraging this information, we show that Dis3’s exonuclease function is required for mitotic cell division: in its absence, cells are delayed in mitosis and exhibit aneuploidy and overcondensed chromosomes. In contrast, we find that modest reduction of dis3 function enhances cell proliferation in the presence of elevated Ras activity, apparently by accelerating cells through G2/M even though each insult by itself delays G2/M. Additionally, we find that dis3 and ras genetically interact in worms and that dis3 can enhance cell proliferation under growth stimulatory conditions in murine B cells. Thus, reduction, but not absence, of dis3 activity can enhance cell proliferation in higher organisms.